Lesson Study Effectiveness in Field Experience Practice in Improving the Pedagogic Competence of Prospective Teacher Students of the Economics Education Study Program, Universitas PGRI Mahadewa Indonesia - Ni Luh Putu Cahayani (IAHN-TP Palangka Raya, 2024)
Pedagogic competence is an important skill for teachers, but it is also important for students who will become teachers when carrying out school field introduction (PLP 2). This research is in the background of the lack of readiness to teach students in the implementation of School Field Introduction activities. This research aims to improve students' understanding of PLP 2 and the pedagogic competence of prospective teacher students in the economic education study program of PGRI Mahadewa University Indonesia. This type of research is qualitative research with which was carried out at the beginning of the August - November 2023 research. The method used in this study is lesson study. Lesson study is carried out through the implementation of Plan, Do and See. The research instruments are in the form of observation sheets and assessment sheets. The subjects of the study were 5 students who had completed PLP for five months at SMA PGRI 4 Denpasar. The data collection techniques are interview, observation, and documentation techniques. The results of the study showed that students experienced an increase in PLP 2 competencies and pedagogical competencies